2013
DOI: 10.1007/s00701-012-1599-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical endoscopy-assisted presigmoid retrolabyrinthine approach as a minimally invasive surgical option for the treatment of medium to large vestibular schwannoma

Abstract: The paper from Iacoangeli and his colleagues from Ancona and Rome in this issue of Acta Neurochirurgica is timely given the continuing controversy on best treatment options for vestibular schwannomas.Their report is on the preliminary experience with an old approach integrated with the endoscope. The case material includes ten cases of small and medium sized sporadic acoustic neuromas (five cases of 8 and 10 mm, five cases of 11-25 mm), selected on the basis of a favourable anatomy of the temporal bone.It is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In 1980, the retrolabyrinthine approach was described as the “direct”[23] route to the CP angle, being well-liked by otologists and neurosurgeons alike, in the treatment of Meniere's disease,[22] petroclival meningiomas,[12] vestibular schwannomas,[47] and in the placement of auditory brainstem implants. [5] In the early 2000s, the retrolabyrinthine approach was described as “the unsung hero of skull base surgery.”[18] When compared to a retrosigmoid approach, the presigmoid exposure provides the benefits of a shorter working distance and less cerebellar retraction.…”
Section: Discussionmentioning
confidence: 99%
“…In 1980, the retrolabyrinthine approach was described as the “direct”[23] route to the CP angle, being well-liked by otologists and neurosurgeons alike, in the treatment of Meniere's disease,[22] petroclival meningiomas,[12] vestibular schwannomas,[47] and in the placement of auditory brainstem implants. [5] In the early 2000s, the retrolabyrinthine approach was described as “the unsung hero of skull base surgery.”[18] When compared to a retrosigmoid approach, the presigmoid exposure provides the benefits of a shorter working distance and less cerebellar retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular schwannomas (VSs) are common benign tumors that represent approximately 80% of tumors of the cerebellopontine angle and 6% of all intracranial tumors 1,2 . Many studies support managing VSs conservatively or via observation because they have found that tumor progression occurs at very slow rates, between 1 and 2 mm/year 3,4 . Hearing loss (HL) is the most common presenting symptom for patients with VSs; more than 90% of patients with VSs have some level of auditory dysfunction when assessed 5,6 .…”
mentioning
confidence: 99%
“…1,2 Many studies support managing VSs conservatively or via observation because they have found that tumor progression occurs at very slow rates, between 1 and 2 mm/year. 3,4 Hearing loss (HL) is the most common presenting symptom for patients with VSs; more than 90% of patients with VSs have some level of auditory dysfunction when assessed. 5,6 Some authors consider observation to result in a high risk of hearing dysfunction as the wait time increases, so early surgery to preserve useful hearing should be the first choice.…”
mentioning
confidence: 99%
“…The surgical approaches used in microsurgery for acoustic neuroma can be summarized as: translabyrinthine, 2,3 enlarged translabyrinthine 4,5 with the possibility of its transapical extension, 5 retrosigmoid, 6 retrosigmoid with retrolabyrinthine meatotomy, 7 presigmoid retrolabyrinthine (an old approach that was recently adapted for use with the endoscopy-assisted technique), 8,9 and the middle cranial fossa approach. [10][11][12] All these approaches involve microsurgical methods, craniotomy or craniectomy, access being first extradural then intradural (translabyrinthine, middle cranial fossa), or intradural with cerebellar retraction (retrosigmoid).…”
mentioning
confidence: 99%